Characterization of an activating R1353H insulin-like growth factor 1 receptor variant in a male with extreme tall height. Issue 2 (August 2018) - Lin, Yingbo; van Duyvenvoorde, Hermine A; Liu, Hongyu; Yang, Chen; Warsito, Dudi; Yin, Chang; Kant, Sarina G; Haglund, Felix; Wit, Jan M; Larsson, Olle
Abstract : Objective: The insulin-like growth factor1 receptor (IGF1R) is important in growth and development, and inactivating IGF1R mutations cause short stature and relatively high levels of serum IGF-I. We identified an unclassified IGF1R R1353H variant in a male with extreme tall height, very low levels of serum IGF-I and delayed and prolonged growth spurt. The index case's mother and three sons all carried the variant, but so far only the eldest son (age 18 years) presented with tall height. We hypothesized that the variant could constitute an activating mutation. Design: The IGF1R R1353H variant was investigated in Igf1r − / − mouse embryonic fibroblasts (R-cells) by cell cycle, colony formation and transcriptome analyses. Results: The IGF1R R1353H (R-1353) exhibited significantly increased cell proliferation, G1-S progression and colony formation in soft agar. RNA sequencing identified 195 differentially expressed genes between R-WT and R-1353 (adjusted P < 1E-100). Most genes were upregulated in R-1353, including the gene encoding the androgen receptor (AR). Gene expression profiling showed the most significant enrichment in extracellular matrix organization ( P = 2.76E-7), collagen biosynthesis ( P = 1.21E-5) and cell adhesion ( P = 7.38E-5). Retrospective biochemical analysis of the index case revealed decreased testosterone and sex hormone-binding globulin levels, whereas LH and FSH were within normal ranges. This profile suggests an increased sensitivity to androgen, which is compatible with the enhanced expression of Ar in R-1353 cells. Conclusions: Our findings suggest that R1353H constitutes an activating IGF1R variant. The possible deregulation of collagen turnover and increased androgen sensitivity implicates an association to tall phenotype in male carriers.